Význam podskupin HDL pro metabolismus a funkci HDL - Asztalos, Bela F; Tani, Mariko; Schaefer, Ernst J (Current Opinion in Lipidology, 2011)
Our purpose is to review recent findings highlighting the metabolic and functional diversity of HDL subspecies. RECENT FINDINGS: HDL heterogeneity - both structural and functional - is the main focus of this review. Recent work indicates that the metabolism and functionality of HDL particles differ greatly among HDL subspecies. With the introduction of new and improved methodology (e.g., proteomics), new aspects of the structural complexity and functionality of HDL have been revealed. It has been confirmed that HDL functions - including, but not limited to decreasing inflammation, apoptosis, macrophage adhesion to the endothelium and insulin resistance - are due to HDL's ability to remove cholesterol from cells (reverse cholesterol transport). A new level of HDL complexity has recently been revealed by investigating the lipid composition of HDL with gas chromatography, gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry. There are about 100 different HDL-associated proteins; however, there are many more lipid species potentially associated with HDL particles. SUMMARY: The most important recent findings disclose that HDL is more complex than previously thought. HDL subclasses differ in physical-chemical properties, protein and lipid composition, metabolism, physiological functions and pathophysiological significance. The staggering complexity of HDL demands significantly more investigation before we can truly begin to understand HDL metabolism and function in humans.
Keywords: financování organizované; Animals; terminologie jako téma; Complement System Proteins; Terminology as Topic; cholesterol; velikost částic; Apolipoproteins; Particle Size; lidé; lipoproteiny HDL; Cholesterol; apolipoproteiny; Financing, Organized; oxidace-redukce; Atherosclerosis; Oxidation-Reduction; ateroskleróza; zvířata; komplement; Lipoproteins, HDL; Humans